Records of Bombus mastrucatus Gerstaecker, 1869 (Hymenoptera, Apidae) in the Kola Peninsula - Grigory S. Potapov; Oleg A. Belyaev; Yulia S. Kolosova (Travaux du Muséum National d’Histoire Naturelle “Grigore Antipa”, 2025)
We present the records of Bombus mastrucatus Gerstaecker, 1869 in the Murmansk Region (Russia). We suppose that the distribution of this species in the region is probably limited to the territory from the vicinity of the town of Kandalaksha to the south of the Kola Peninsula along the Kandalaksha Gulf.